STUDI ANALISIS PEROLEHAN GAS HIDROGEN DAN OKSIGEN PADA PROSES ELEKTROLISIS H2O - Yanra Richardo; Anggun Anugrah; Sepannur Bandri; Andi Sofyan (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
The need for fuel resources is increasingly significant, but currently, existing fuels produce a lot of exhaust gases that are not environmentally friendly. For this reason, there need to be other fuel sources that have zero emissions. One of them is an H2 (Hydrogen) and O2 (Oxygen) gas. There are many ways to obtain these alternative fuels. In this research, the author uses the electrolysis method on H2O to be able to separate hydrogen gas (H2) and oxygen gas (O2) from the water quickly and efficiently which will help in replacing fossil fuels that are not environmentally friendly. From the research that the author did by varying the electrode materials of copper, aluminum, stainless steel, and tin and varying the electrode surface area in distilled water-electrolyte liquid (pure water), the author found that H2 and O2 gases are more produced if using a stainless steel material on the anode and cathode. The author also found that the volume of gas produced is directly proportional to the electrode surface area and the potential difference between the electrodes.